Transformation of Directional Wave Spreading in the Surf Zone Using Video Image Data - Zikra, Muhammad; Hashimoto, Noriaki; Yamashiro, Masaru; Suzuki, Kojiro (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2014)
In present study, video images technique is used to investigate the transformation of the directional wave spreading in shallow water. The technique is based on time series of the pixel brightness on video images. The Bayesian Directional Method is conducted in estimating the directional wave spectrum for evaluating the change of the directional wave spreading in the surf zone area. Video image data recorded at Hasaki beach in Japan are used in the analysis. Estimation of principle direction and spreading parameter in the surf zone regions indicated that principle directions at peak frequency are not strongly affected by wave breaking process. In contrast, the broadenings of directional spreading were observed when the waves start breaking on the sand bar and toward the shore area.